Inter-agency collaboration in building urban fire resilience in Indonesia: how do metropolitan cities address it? - Harakan, Ahmad; Hilman, Yusuf Adam; Karso, A. Junaedi; Awaluddin, Awaluddin; Nurhalijah, Nurhalijah; Muin, Indah Sidrawaty; B, Aldy Nurdiansyah; Fadillah, Arfan; Hardi, Rudi (Frontiers in Sustainable Cities, 2025)
IntroductionUrban fire disasters pose a significant challenge to city resilience and sustainability, particularly in the Global South, where rapid urbanization exacerbates existing vulnerabilities. In Indonesia, recurring fire incidents, ranging from forest fires to residential fires in densely populated areas, highlight the urgent need for effective fire disaster management. This study focuses on Makassar, a metropolitan city facing increasing fire risks due to high population density, aging infrastructure, and limited preparedness.MethodsThis research employs a qualitative approach, drawing on fire incident data from 2018 to 2023, interviews, and historical analysis to assess collaboration mechanisms in fire disaster management. The study examines inter-agency coordination, communication gaps, and resource allocation issues, which hinder effective disaster response.ResultsFindings reveal a concerning rise in fire incidents in Makassar, leading to significant socio-economic impacts, including fatalities and property damage. The study identifies critical deficiencies in inter-agency collaboration, largely due to differing organizational cultures, inadequate coordination mechanisms, and resource distribution challenges.Discussion and conclusionBy evaluating global fire resilience models, the research proposes a governance framework to enhance inter-agency cooperation in Makassar. The study advocates for integrated strategies, combining infrastructure development with community-driven initiatives to strengthen disaster prevention, response, and recovery. These findings contribute to sustainable urban development, ensuring greater resilience against fire disasters in rapidly urbanizing cities.